Karakteristik Nilai Kalor Briket Campuran Tebu Tibarau dan Kulit Durian - Hendri Nurdin; Waskito Waskito; Darmawi Darmawi (invotek, 2019)
Increased energy needs in the community can have an impact on the scarcity of fuel oil so that it becomes a dependence on energy as a main requirement. The development of product diversification in the form of mixed sugar cane and durian skin briquettes in an effort to obtain alternative fuels. Renewable energy sources that have the potential to be used as fuel for briquettes made from raw sugar cane and durian skin. Efforts and innovations of mixed sugar cane and durian skin briquettes are produced as alternative fuels so that they have characteristics of quality and performance, namely the calorific value. The stages of testing and evaluation of mix sugar cane and durian skin briquettes are needed before being developed and recommended as alternative fuels. Through the technology of the process of making briquette products with compacting and optimizing the content composition and use of adhesive types to obtain the heating value. From this study can be produced mixed sugar cane and durian skin briquettes which are recommended as alternative fuels. The highest characteristics of the heating value of mixed of sugar cane and durian skin briquettes with gambir adhesive were obtained at 16967.91 kJ/Kg and density of 682.23 Kg/m3. Briquettes (biomass) that have a high density have a high calorific value. Comparison of the composition of the mixture in making briquettes is 40%: 40%: 20%. The composition of the mixture between the raw material and the adhesive, the amount of grain, the force of compacting greatly affects the characteristics of the calorific value and density of the briquettes.